Serotonin Syndrome with Monotherapy of Low-Dose Sertraline in an Adult Patient with Autism Spectrum Disorder - Madan, Rohit; Platto, Jody; Manoharan, Senthil Rajaram; Monga, Varun (Case Reports in Psychiatry, 2023)
Serotonin syndrome, also known as serotonin toxicity, is associated with increased serotonergic activity in the central and the peripheral nervous system. The symptoms can range from mild to potentially life threatening. Given the widespread use of serotonergic agents, the number of cases is on the rise. It is seen with therapeutic medication use, inadvertent interactions between drugs, and intentional self-poisoning, but still known cases with monotherapy of selective serotonin reuptake inhibitors are uncommon. Another known fact is that elevated whole blood serotonin, or hyperserotonemia, is one of the first biomarkers identified in autism spectrum disorder and is present in more than 25% of affected children. We present a case of a 32-year-old male with a history of autism spectrum disorder and depressive disorder who presented to the emergency department with restless agitation, neuromuscular excitability, and autonomic instability. He had been prescribed sertraline 50 mg which he had taken daily as prescribed for 4 days. On the fourth day, he presented to the emergency department with diffuse muscle stiffness, upper extremity tremors, ocular clonus, and inducible ankle clonus. He was diagnosed with probable serotonin syndrome utilizing Hunter’s criteria. Patient’s symptoms resolved within 24 hours with intravenous fluids, lorazepam, and discontinuation of sertraline. This case highlights the importance of a high degree of clinical suspicion in patients even on monotherapy of selective serotonin reuptake inhibitors in therapeutic doses, especially in children and adults with autism spectrum disorder. Due to preexisting hyperserotonemia, they may be more susceptible to serotonin syndrome than the general population.